RETHINKING HEIDEGGER'S DWELLING THROUGH ARABIC LINGUISTICS - El Moussaoui, Mustapha Hashem (Journal of Islamic Architecture, 2020)
Inhabiting a space or dwelling has been a debatable terminology in architectural theory practice. Martin Heidegger's conference paper "Building dwelling thinking" is a major philosophical work that influenced architects in the 20th century. The philosopher interpreted the word as an etymological archaeologist, working on the word's essential meaning until he related it to, Being-in-this-world and Being-towards-death. In this research, we examine the term "dwelling" through the Arabic parables "Maskan" and "Manzel" to reach a more comprehensive understanding that will unveil its essential meaning in its local cultural context. Moreover, we base our research on a survey answered in Lebanon, on the meaning of the word Maskan in its contemporary form, while linking it to Heidegger's etymological findings. Our results explicitly an Arabic term used that describes a different phenomenon in other cultures.